Sosialisasi Teknologi Pengering Hasil Perkebunan Berbasis PLTMH di Pesawaran Indah - Harmen, Harmen; Fitriawan, Helmy; Irsyad, Muhammad; Prayitno, Hadi (Penerbit Goodwood, 2025)
Purpose: The purpose of this community service program in Pesawaran Indah Village is to introduce sustainable drying technology powered by Micro-Hydro Power Plants (PLTMH) to improve the efficiency and quality of post-harvest processing in the village's coffee, cocoa, clove, and nutmeg farming sectors. Methodology: The program utilized a community-based approach that involved socializing the benefits of PLTMH-powered drying technology, determining strategic locations for its implementation, and constructing a drying machine with a capacity of 4 x 20 kg. The program also focused on enhancing the community's knowledge of energy sources and drying techniques through workshops and discussions. Results: The program successfully increased community awareness of energy-efficient drying technology, with understanding rising from 20% to 80%. The construction of the drying machine was completed, and the community was encouraged to adopt this technology, which is expected to enhance agricultural product quality, promote sustainable energy use, and empower local farmers. Conclusion: The program effectively introduced a sustainable technology that supports local agricultural practices and promotes the use of renewable energy. The adoption of this technology is expected to benefit the community by improving post-harvest processing and increasing the value of agricultural products. Limitations: The program's scope was limited to a small-scale implementation, and further efforts are needed to monitor its long-term impact on product quality and community adoption. Contribution: This community service program contributes to promoting sustainable agricultural practices and renewable energy use in rural communities, offering a model for enhancing local economic development through appropriate technology.